One-bit quantified phase-based algorithm for three-dimensional localization of wideband near-field source via uniform circular array - Hu, Panhe; Chen, Xin; Su, Xiaolong; Shi, Junpeng; Liu, Zhen (Journal of applied remote sensing, 2022)
We present a one-bit quantified phase-based algorithm combined with the noiseless correlation transformation (PANCT) to estimate the three-dimensional (3D) parameters (i.e., azimuth angle, elevation angle, and range) of wideband near-field source via uniform circular array. We first propose a noiseless correlation transformation scheme without direction of arrival pre-estimation to obtain the correlation matrix of focusing frequency bin. Then, we exploit the phase differences to construct indefinite matrix and implement the least-square method to derive 3D parameters. Considering that the complexity scenarios include phase ambiguity and one-bit quantization, we further propose the corresponding unambiguous PANCT algorithm and one-bit quantified PANCT algorithm, respectively. Simulation results demonstrate that the proposed algorithms provide satisfactory estimation performance with low computational complexity.